2021
DOI: 10.1101/2021.11.24.469833
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertebrate extracellular matrix protein hemicentin-1 interacts physically and genetically with basement membrane protein nidogen-2

Abstract: Hemicentins are large proteins of the extracellular matrix that belong to the fibulin family and play pivotal roles during development and homeostasis of a variety of invertebrate and vertebrate tissues. However, bona fide interaction partners of hemicentins have not been described as yet. Here, applying surface plasmon resonance spectroscopy and co-immunoprecipitation, we identify the basement membrane protein nidogen-2 (NID2) as a binding partner of mammalian hemicentin-1 (HMCN1), in line with the formerly d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Given the critical role of type IV collagen in mediating B-LINK maintenance, we wanted to determine how hemicentin promotes collagen assembly. Hemicentin is not known to bind to type IV collagen ( Zhang et al, 2021 Preprint ), so we hypothesized that hemicentin might recruit another protein that mediates collagen assembly. We reasoned that loss of this protein would result in a similar phenotype to type IV collagen loss and thus compiled a list of 403 genes using Wormbase (see Materials and methods) whose RNAi knockdown or genetic loss leads to the Rup phenotype ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the critical role of type IV collagen in mediating B-LINK maintenance, we wanted to determine how hemicentin promotes collagen assembly. Hemicentin is not known to bind to type IV collagen ( Zhang et al, 2021 Preprint ), so we hypothesized that hemicentin might recruit another protein that mediates collagen assembly. We reasoned that loss of this protein would result in a similar phenotype to type IV collagen loss and thus compiled a list of 403 genes using Wormbase (see Materials and methods) whose RNAi knockdown or genetic loss leads to the Rup phenotype ( Table S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Close association of hemicentin with fibulins and collagens has been observed in both C. elegans and vertebrates ( Feitosa et al, 2012 ; Lin et al, 2020 ; Muriel et al, 2005 ). The physical-binding partners of hemicentins, however, are poorly understood ( Zhang et al, 2021 Preprint ). Studies in C. elegans have shown that hemicentin promotes the assembly of fibuilin-1 at several extracellular sites and requires EGF repeats 4 and 5 of fibulin-1, suggestive of a direct interaction ( Muriel et al, 2005 , 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Close association of hemicentin with fibulins and collagens have been observed in both C. elegans and vertebrates (Feitosa et al, 2012;Lin et al, 2020;Muriel et al, 2005). The physical binding partners of hemicentins, however, are poorly understood (Zhang et al, 2021). Studies in C. elegans have shown hemicentin promotes the assembly of fibuilin-1 at several extracellular sites and requires EGF repeats 4 and 5 of fibulin-1, suggestive of a direct interaction (Muriel et al, 2005(Muriel et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%